An Analysis of Students’ Mistakes in Reducing Adjective Clause in Thesis Backgrounds - Kindi Naufal Athallah; Witri Oktavia (Universitas Negeri Padang, 2023)
Grammar plays a crucial role in research writing, as clear and well-structured sentences are essential for effectively conveying meaning to readers. The objective of this study is to find out the mistakes which the students commonly make in reducing adjective clause in thesis background. The population of this research were English Department of UNP students’ thesis with 50 theses in total. The sample were 50 theses chosen by using total sampling. This research used descriptive research. According to the data found, it can be seen that the most mistake in writing adjective clause reduction made by students is reduction of adjective clause with verb in passive voice with 17 mistakes, followed by reduction of clause with verb in active voice with 3 mistakes made and no mistakes made in reduction of clause with verb in perfect tense because the researcher found no adjective clause reduction with verb in perfect tense made by students. In addition, the percentage of mistakes made by students in reducing adjective clause was 12.12% of 165 reduced adjective clauses found.